1991
DOI: 10.1159/000288417
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Hypochondriacal Fears and Beliefs

Abstract: Any undue concern with bodily function is often labeled as hypochondriacal. Kellner’s Illness Attitude Scales, self-rating instruments, distinguish between generic worry about illness, concern about pain, health habits, hypochondriacal beliefs, thanatophobia, disease phobia, and bodily preoccupations. The Illness Attitude Scales have been used in a number of studies concerned with patients suffering from DSM-III-R hypochondriasis, panic disorder, melancholia, in the medically ill, in pregnant women, during med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
7

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 20 publications
(29 reference statements)
2
26
0
7
Order By: Relevance
“…Another 44 patients had high pre-treatment scores on two hypochondriasis scales, the Illness Attitude Scales (IAS) and the Whiteley Index (WI). The IAS was originally developed by Kellner [25, 26]; see also 27]and consists of 29 items which are to be rated on five-point Likert scales. Although Kellner had originally defined nine a-priori scales with three items per scale, a re-analysis reported by Speckens et al [21]and confirmed by us [28]suggests that two main dimensions labeled ‘health anxieties’ and ‘illness behavior’ can be differentiated.…”
Section: Methodsmentioning
confidence: 99%
“…Another 44 patients had high pre-treatment scores on two hypochondriasis scales, the Illness Attitude Scales (IAS) and the Whiteley Index (WI). The IAS was originally developed by Kellner [25, 26]; see also 27]and consists of 29 items which are to be rated on five-point Likert scales. Although Kellner had originally defined nine a-priori scales with three items per scale, a re-analysis reported by Speckens et al [21]and confirmed by us [28]suggests that two main dimensions labeled ‘health anxieties’ and ‘illness behavior’ can be differentiated.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation between abnormal illness behavior and health habits may have implications in preventive efforts. Indeed, individuals with hypochondriacal fears and beliefs were found to take worse care of their health than control subjects in several studies [167]. They may be so distressed by their belief of having an undiagnosed or neglected disease that behaviors that may yield benefits in the distant future appear to be irrelevant to them.…”
Section: Application Of Psychological Therapies To Medical Diseasesmentioning
confidence: 99%
“…Curiosamente, pacientes hipocondría-cos só não se diferenciariam dos não-hipocondríacos em rela-Pânico e hipocondria Torres AR et al ção a hábitos de saúde, ou seja, não se cuidariam melhor. Para Kellner et al, 10 isto se deve ao fato de que a idéia perturbadora de já estar com uma doença grave não diagnosticada poderia levá-los a negligenciar comportamentos que visassem benefí-cios futuros para a saúde.…”
Section: Problemas Conceituais E Critérios Diagnósticosunclassified
“…ex., alimentares, em relação ao fumo), apesar de mais preocupados com doenças, como descrito na hipocondria primária. 10 Além disso, 48% deles tinham algum problema físico, como asma, hipoglicemia ou hér-nia de hiato (significativamente mais que os outros grupos).…”
Section: Ocorrência De Sintomas Hipocondríacos No Transtorno De Pânicounclassified
See 1 more Smart Citation